The Epigenesis of Morality: Kant’s Moral Philosophy between Canon and Groundwork for the Metaphysics of Morals - Kobe, Zdravko (Filozofski vestnik, 2016)
The paper examines the development of Kant’s moral philosophy at the time of Critique of Pure Reason. By relying mostly on the so-called reflections, it argues that in the middle of the 1770s Kant was in possession of a rather comprehensive theory of morality as worthiness to be happy, built upon the universalisation of happiness and leading immanently to a moral theology. Even before the publication of Critique this conception was, mainly due to a closer definition of the concept of happiness that now included intellectuality, freedom, and self-satisfaction, reformulated into a system of the epigenesis of happiness out of the laws of freedom. The reflections from the early 1780s suggest the existence of yet another phase, as this conception was further developed into a system of the epigenesis of pure morality which, by drawing a pronounced parallel between cognition and action, now tried to establish the unconditional obligation by examining the a priori conditions of the unity of the willing of a finite rational being. Although the project appears highly promising, inherently consistent, and outwardly in complete agreement with the framework of a critical theory of cognition, it was unexpectedly given up – presumably under the influence of Rousseau and possibly as an overreaction to Garve. But since according to the author the final version of Kant’s moral theory basically implies a pre-critical subject of action, the paper concludes by suggesting that a truly consequent reconstruction of critical moral philosophy requires a reintroduction of the elements once given up by Kant.